Evaluation of Demineralized Freeze- Dried Bone in Augmentation of Buccal Defects during Implant Placement - Tabrizi, Reza; Mir Mohammad Sadeghi, Hassan; Hashemzadeh, Hooman; Jafari, Saba (Regeneration, Reconstruction & Restoration (Triple R), 2016)
Introduction: Bone thickness in the anterior of the maxilla is one of the major concerns for implant placement. The aim of the present study is to evaluate stability of demineralized freeze- dried bone (DFDB) graft for augmentation of buccal defects during implant placement at the anterior of the maxilla using cone-beam computed tomography (CBCT). Materials and Methods: The DFDB graft was used for augmentation of buccal defects during implant placement at the anterior of the maxilla. The amount of remnant DFDB was measured in three points: Coronal, middle and apical portion of the buccal sides of implants after one year. Results: Twenty-two samples were included in this study. All of the exposed implants were osseo-integrated. A significant difference was detected for remnant grafting bone in the coronal and apical portion of the implants between the central site and the lateral site (P<0.05) without any difference in the middle portion. Analysis of data did not show any differences of remnant grafting bone thickness among one-third coronal ,one-third middle and one-third apical portion of the buccal sides of implants after one year (P>0.05). Conclusion: DFDB could be used successfully for augmentation of buccal defects during implant placement. It is assumed that approximately 50% of DFDB is resorbed one year after grafting. The recipient site may influence the amount of resorption rate.